Impact of environmental attitude and materialism on apparel disposal intention. Issue 1 (February 2021) - Cao, Hongrui; Shao, Peng
Abstract: Sustainability is an important rising trend in the apparel industry. Accordingly, this study focuses on the influence of environmental attitude, materialism, channel integration, and other factors on apparel disposal recycling intention in an omni-channel retailing environment. The main findings are as follows: materialism has a significant positive impact, channel integration quality has a significant negative impact, and environmental attitude has no significant impact on impulsive consumption. Next, environmental attitude, impulsive consumption, and channel integration exert significant positive effects on used apparel recycling intention. Finally, improving channel consistency could increase female consumers' willingness to recycle used clothes more than that of male consumers.